Estereotipación en la mujer en el reality Show Baila La Noche - canal 1 - Carriel Viteri, Maria Mercedes (2019)
Television is one of the most widely seen mass media in recent times with the passing of time female nature has been highlighted in the media, showing an image of women related to stereotyping, highlighting the parameters of beauty imposed by themselves. This research shows how in recent years women have been used as a sexual symbol to obtain ratings and impose certain parameters that are reflected in these contents catalogued as entertainment in this case the reality shows who enjoy great impact in the society taking as base the program reality Ecuadorian Baila the night transmitted by the signal of Channel one of Monday to Friday in the hours of 10 pm to 12 am. In this work it was carried out through surveys carried out to a group of 67 people and an interview with Melissa Celsi former participant of the reality Baila the night, leading us to conclude the existence of gender stereotyping within the program and how these use the female image as an object of attraction to engage an audience